2020
DOI: 10.1177/1178223420972363
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cryoablation: Assessment of the Impact of Fundamental Procedural Variables in an In Vitro Human Breast Cancer Model

Abstract: Introduction: Breast cancer is the most prominent form of cancer and the second leading cause of death in women behind lung cancer. The primary modes of treatment today include surgical excision (lumpectomy, mastectomy), radiation, chemoablation, anti-HER2/neu therapy, and/or hormone therapy. The severe side effects associated with these therapies suggest a minimally invasive therapy with fewer quality of life issues would be advantageous for treatment of this pervasive disease. Cryoablation has been used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
2
10
0
2
Order By: Relevance
“…The occurrence of breast cancer is much higher than any of these other types of cancer [20]. To eradicate the cancer from the body, various therapies have been tested, such as chemotherapy [23], hormone therapy [24], radiotherapy [25], immunotherapy [26], stem cell therapy [27], proton beam therapy [28], clinical trials [29], and cryoablation [30], etc. Surgery is also an option to remove the cancer cells from a specific organ in the body [31].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of breast cancer is much higher than any of these other types of cancer [20]. To eradicate the cancer from the body, various therapies have been tested, such as chemotherapy [23], hormone therapy [24], radiotherapy [25], immunotherapy [26], stem cell therapy [27], proton beam therapy [28], clinical trials [29], and cryoablation [30], etc. Surgery is also an option to remove the cancer cells from a specific organ in the body [31].…”
Section: Introductionmentioning
confidence: 99%
“…Three-cycle protocols were chosen for lung lesions, as previously described in the literature [ 11 ]. A previous study showed that the thawing process (both active and passive) did not impact tissue damage [ 19 ], but more recent studies have demonstrated that active thawing resulted in increased cell survival, and thereby less effective ablation, as compared with passive thawing [ 20 ]. In our study, passive thawing was performed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 0°C degree was used as the control temperature for non-freezing conditions. Freezing for 10 min was the time necessary for the media to be frozen while preserving the integrity of the cells ( 53 ). A temperature of 0°C was achieved by placing the cells on a MyBlock™ Mini dry bath with cooling (Benchmark Scientific, Inc.) and −13°C temperature was achieved by placing the cells in a Sanyo temperature calibrated freezer (Sanyo Electrical Co. Ltd.), while the control temperature was achieved by maintaining the cells in a humidified 5% CO 2 atmosphere at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The lowest temperature that could be used to accomplish freezing while maintaining cell viability was -13˚C. In a previous study, a temperature of -10˚C resulted in a high cell survival rate, whereas -15˚C led to >80% cell death (53). In addition, 0˚C degree was used as the control temperature for non-freezing conditions.…”
Section: Inhibition Of Aquaporins As a Potential Adjunct To Breast Cancer Cryotherapymentioning
confidence: 99%